Novel aerobic granulation technology for high-performance industrial wastewater treatment - Liu, Yu. (2008)
In this research work, the effects of hydrodynamic shear force, substrate concentrations, and hydraulic retention time on aerobic granulation in sequencing batch reactor (SBR) were studied. Meanwhile, the strategy for improving stability of aerobic granules was also investigated and the potential of aerobic granules as novel biosorbent for soluble metal removal was also looked into.